A DESIGN OF A PLAIN RELIEF COMMUNICATION GUIDANCE TOOL FOR THE BLIND PEOPLES - Donna Nurhaida Masdiana Sirait; Darmeli Nasution (Jurnal Scientia, 2023)
A Blind people with visual impairments, tools to carry out activities are needed. If they do not use assistive devices, blind people will experience difficulties when carrying out daily activities such as reaching obstacles that are near them. As for those who use tools that are still classified as manual, such as sticks made of stainless steel. However, the stick is considered less effective because the reach of the stick is not so wide and long, it is also less efficient when used in the midst of the activities of people nearby. On the basis of these problems this research was conducted to help blind people be aware of the obstacles around. In this paper discussed an use of the HC-SR04 sensor functions as a detector for objects or holes in front that block the blind while walking. While the use of the buzzer on the blind aids is used as a sound output. The output sound produced is when the critical distance is less than 100 cm, the buzzer will sound and the blind must be aware that there is an object or hole in front. But it will be different if the distance is more than 100 cm then the road ahead is safe in the sense that the blind can continue walking.